Water‐Soluble Gold(III)–Metformin Complex Alters Mitochondrial Bioenergetics in Breast Cancer Cells. (28th July 2021) - Hyun Kim, Jong; Ofori, Samuel; Mertens, R. Tyler; Parkin, Sean; Awuah, Samuel G.
Abstract: Chemical control of mitochondrial dynamics and bioenergetics can unravel fundamental biological mechanisms and therapeutics for several diseases including, diabetes and cancer. We synthesized stable, water‐soluble gold(III) complexes (Auraformin) supported by biguanide metformin or phenylmetformin for efficacious inhibition of mitochondrial respiration. The new compounds were characterized following the reaction of [C N]‐cyclometalated gold(III) compounds with respective biguanides. Auraformin is solution stable in a physiologically relevant environment. We show that auraformin decreases mitochondrial respiration efficiently in comparison to the clinically used metformin by 100‐fold. The compound displays significant mitochondrial uptake and induces antiproliferative activity in the micromolar range. Our results shed light on the development of new scaffolds as improved inhibitors of mitochondrial respiration. Abstract : Controlling mitochondrial dynamics : Newly developed organogold(III)‐Metformin complexes inhibit mitochondrial respiration to induce antiproliferative activity in breast cancer cells. We anticipate that the use of delocalized lipophilic cations from gold cyclometalation to Metformin may enhance selective uptake in cancer cells to target energy sensing bioenergetic pathways in cancer.